THE INFLUENCE OF TWO MODELS OF PHYSICAL EDUCATION PLANNING ON SPORT-TECHNICAL KNOWLEDGE OF SECONDARY SCHOOL FEMALE STUDENTS - Živorad Marković; Dragoljub Višnjić; Dragan Martinović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The goal of this research was to determine eventual difference between continuo- us and concentrated model of planning and realization of program contents of Physical Education in relation to sport-technical knowledge of female students. This research was educational experiment with longitudinal character on the specimen of 92 fema- le examinees divided into two sub specimens - according to the criterion of realization of program contents of Physical Education lesson: experimental group with 50 female examinees and control group with 42 secondary school female examinees of year one. Sport-technical knowledge was evaluated with ten variables. Multivariant analysis of the variance, Roy's test, discriminative analysis and descriptive analysis were applied in processing of data which were acquired by empirical research. Statistically significant differences , in favor of experimental group in all ten researched variables, indicate that the contents of experimental treatment resulted in positive effects in sport-technical knowledge of female students in experimental group.